Obstetric and perinatal aspects in patients with congenital heart diseases - Oliveira, Tenilson Amaral (1996)
The benefits of surgical treatment for patients with congenital heart disease in relation to pregnancy are still controversial. We studied 48 pregnant women (mean age = 25 years) with surgically-corrected congenital heart diseases (Group 1). This included 15 cyanotic diseases: Fallot's tetralogy (11 cases); Ebstein's anomaly (2 cases); transposition of the great arteries (1 case); and double outlet of the right ventricle (1 case). We compared them to 52 pregnant women (mean age = 26 years) with untreated congenital heart diseases, which included 11 cases of Eisenmenger's syndrome (Group 2). Group 2 showed a higher incidence of maternal death (12 vs. 0 percent; p=0.01), perinatal mortality (15 vs. 0 percent; p=0.01) and prematurity (32 vs. 7 percent; p=0.01). Spontaneous abortion (4 vs. 10 percent), Caesarean deliveries (48 vs. 66 percent) or growth retardation (13 vs. 28 percent) did not present any significant differences between these groups. Surgical treatment in patients with heart diseases is associated with a better maternal and fetal prognosis. Therefore, surgery must be considered when counseling patients with congenital heart diseases.